2014
DOI: 10.2298/sarh1406306p
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results after complete surgical correction of transposition of the great arteries

Abstract: Arterial switch operation has been successfully performed at our institution, with acceptable perioperative mortality and excellent late outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In our study, simple TGA was found to be slightly more common than the complex forms, a finding which agrees with postnatal series [6,28] but that contrasts with previous prenatal studies reporting that the latter are more common [22]. These discrepancies may be attributed to the degree of distortion of cardiac anatomy that both types of TGA have, and hence, the ease of prenatal detection.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, simple TGA was found to be slightly more common than the complex forms, a finding which agrees with postnatal series [6,28] but that contrasts with previous prenatal studies reporting that the latter are more common [22]. These discrepancies may be attributed to the degree of distortion of cardiac anatomy that both types of TGA have, and hence, the ease of prenatal detection.…”
Section: Discussionsupporting
confidence: 75%
“…Although TGA situates among the major CHD with the best outcome results [4], the survival rate reported differs widely between series, from 75-80% to 98-99%, depending on factors such as the type of TGA or the presence of coronary anomalies [5,6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…The majority (79.5%) of patients underwent neonatal arterial switch. At the time of operation, the median age was 13 days (IQR, [9][10][11][12][13][14][15][16][17][18][19][20][21][22], and the median weight was 3.5 kg (IQR, 3.2-3.9). The most frequent prior procedure was a Rashkind balloon atrial septostomy performed in 62 (48.8%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…Shim et al reported an astonishing mortality rate of 2.2% among a cohort of 139 patients who underwent an arterial switch operation between 1995 and 2014 in South Korea [ 15 ]. However, other authors from small and medium case-load centers have reported overall surgical mortalities ranging from 4.8 to 28% [ 14 , 20 , 21 , 22 ]. Similar to the experience of large centers, surgical mortality rates tend to decrease with time [ 14 , 15 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation